An integrated optimization model for the layout design of a subsea production system. (August 2018) - Hong, Cheng; Estefen, Segen F.; Wang, Yuxi; Lourenço, Marcelo Igor
Highlights: An integrated model is proposed to optimize the layout of the subsea production system. Seabed topography and obstacles are taken into consideration. The simulated annealing and Dijkstra algorithms are coupled to solve the model. The model was applied to the layout design of a field with 22 wellheads and one FPSO. Fluid flow issues could be linked to the model for further optimization. Abstract: A properly arranged subsea production system reduces costs and contributes to production performance due to favorable hydraulic characteristics and flow assurance. Therefore, the layout design of subsea production systems is very important in offshore field development. The design of these systems mainly includes locating the subsea facilities, determining the subsea topology and identifying the pipe route. Each of these three aspects have been studied, for instance, optimization of the pipe network or identification of the optimal single pipe route. However, the combination of these three aspects has not yet been discussed in detail. This paper presents an integrated optimization model for the layout design of a wellhead-manifold-FPSO system, with the aim of obtaining a minimum total pipe length. There are two key details of this model that distinguish it from other models. The first detail is that the seabed topography and obstacles are taken into consideration. The second detail is that all three abovementioned aspects are considered together in the model to determine the optimal number of manifolds, manifold and riser base positions, pipe network topology and pipe routes. The simulated annealing and Dijkstra algorithms are coupled to solve the model by using a newly proposed process. The application of this method is demonstrated by designing the layout of an oil field with 22 wellheads and one FPSO. The results are compared with the situation that neglects the seabed topography, showing a difference in suggested pipe length. In addition, the pipe route effect on both hydraulic and flow assurance is briefly discussed. The model provides a method to link related issues of interest to the layout design, resulting in a practical subsea layout that can be used to more reliably estimate costs, more accurately describe multiphase flow and help in decision-making for flow assurance.